PENGARUH USIA DAN STATUS GIZI TERHADAP KETAJAMAN PENGLIHATAN - Nur Ulfah; Siti Harwanti; Ngadiman Ngadiman (Jurusan Kesehatan Masyarakat dan Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2013)
ABSTRACT One aspect that should be a concern for employers is the comfort of working labor when carrying out their work. Convenience is meant here is comfort working position, temperature comfort, visual comfort, and convenience of audio. If the comfort of the visual can be obtained on a building, then the object to be viewed or in the field of lighting is known as a visual task, you will see clearly without eye has to work hard, so that workers can carry out visual tasks well during their work time (Atmodipoero, 2000). The general objective of this research is to investigate the relationship between age, nutritional status with visual acuity. The results showed that the age had relationship with visual aquity and no relationship between nutritional status with visual aquity. Suggestion for the company is necessary to add lighting to meet minimum standards in the workplace section Knitting, necessity of providing health insurance for health care of eyes, especially the elderly for the efficiency of his eyesight did not continue to decline should be occur rotation system of labor have which has been decreased visual acuity of the knitting to another section. Key words: acuity of vision, labor, knitting Kesmasindo, Volume 6, Nomor 1 Januari 2013, Hal. 75-84